Salesman Performance Monitoring Apllication For Achievement of Sales Target Of CV Bharata Sport & Fashion Based Website - Mahesayasa, Kadek Dwi; Wulandari, Sri Hariani Eko; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Bharata Sport & Fashion is a company act in the sales of sports equipment and sports clothing which was built in 1986 on Jl. Ngurah Rai no.36, Jembrana Bali This company currently has some problems namely: 1) bonus counting process, work performance and making report of Salesmen performance that are still done manually that leads to a delay in reporting process and there is a risk to lost the data because it was saved in Ms Excel. 2) reservation process is still using telephone as a communication media and the reservation record is written in the notebook. This proses needs a lot of budget. 3)Â  this company has difficulty in monitoring their Salesmen in some branches of the company because one and another are located in long distance. The solution offered for covering those problems are making an application of Salesmen performance that included to make the visiting schedule, to report the visiting result, to record the customerâ€™s reservation and to calculate bonus and salesman performance. The result of this essay show that application can help do generate sales report, the monitoring of Salesmen performance, counting the bonus, and this application can show the graphic of sales, bonus, salesman performance in each branch office.